Offices and planning in Brussels, a half-century of missed opportunities? - Michel De Beule (Brussels Studies)
The relationship between offices and planning in Brussels could be summed up as a series of missed opportunities. Decisions were taken blow by blow, without truly taking account of what had been planned. This real estate game, which has been going on for half a century, has had sometimes obscure causes, often unspoken motives, but reasons that have always been logical for at least one of the four players involved in the overall misunderstanding, i.e., promoters, national government (and then federal and regional governments), local officials, and the residents themselves. Planning long remained officious, with attempts made to intervene in strips. Even though the authorities made a relevant planning proposal starting in 1958, the future European Quarter was created in silence and without directives. With the country’s subdivision into regions planning became official, but the building of offices nevertheless came in for little supervision. In 1999, more than twenty years after the adoption of Brussels’s first area plan, 47% of the some 10 million square metres of offices in Brussels (in edifices with at least 1 000 m² of office space, and thus very often monofunctional buildings) was outside the administrative zones that the area plan had set. Another form of planning went into effect in 1995, but the relationships amongst the players of the real estate game remain ambiguous. The four-party misunderstanding continues.